Kidney cancer PDOXs reveal patient‐specific pro‐malignant effects of antiangiogenics and its molecular traits - Lidia Moserle; Roser Pons; Mar Martínez‐Lozano; Gabriela A Jiménez‐Valerio; August Vidal; Cristina Suárez; Enrique Trilla; José Jiménez; Inés de Torres; Joan Carles; Jordi Senserrich; Susana Aguilar; et al. (EMBO Molecular Medicine)
Abstract An open debate in antiangiogenic therapies is about their consequence on tumor invasiveness and metastasis, which is undoubtedly relevant for patients currently treated with antiangiogenics, such as renal cell carcinoma patients. To address, this we developed an extensive series of 27 patient biopsy‐derived orthotopic xenograft models (Ren‐PDOX) that represent inter‐patient heterogeneity. In specific tumors, antiangiogenics produced increased invasiveness and metastatic dissemination, while in others aggressiveness remained unchanged. Mechanistically, species‐discriminative RNA sequencing identified a tumor cell‐specific differential expression profile associated with tumor progression and aggressivity in TCGA RCC patients. Gene filtering using an invasion‐annotated patient series pinpointed two candidate genes, of which ALDH1A3 differentiated the pro‐invasive subtype of Ren‐PDOXs. Validation in an independent series of 15 antiangiogenic‐treated patients confirmed that pre‐treatment ALDH1A3 can significantly discriminate patients with pro‐aggressive response upon treatment. Overall, results confirm that effects of antiangiogenic drugs on tumor invasion and metastasis are heterogeneous and may profoundly affect the natural progression of tumors and promote malignancy. Furthermore, we identify a specific molecular biomarker that could be used to select patients that better benefit from treatment.